Pancreaticopleural Fistula as a Presentation of a Pancreatic Neoplasm. A Report of a Case and Review of the Literature - Redmond, Ciaran E; McEvoy, Sinead H; Cullen, Anthony; Skehan, Stephen J; Conlon, Kevin C (JOP. Journal of the Pancreas, 2015)
No abstract available. Image: Dilatation of the main pancreatic duct at coronal CT.